COMPRESSION - DISTRACTION OSTEOGENESIS WITH ILIZAROV APPARATUS IN THE TREATMENT OF TIBIAL NON-UNIONS WITH BONE DEFECTS - Sheshoski, Ognen; Stojmenski, Slavcho; Atanasov, Nenad; Micunovic, Micun; Ivanoski, Slavcho; Smicheski, Jordan; Chamovska Sheshoska, Hristina (Journal of Morphological Sciences, 2021)
Treatment of the long bones defects and non-unions are among the most challenging cases to solve in the orthopaedic surgery. In these rare and difficult cases the method of compression - distraction osteogenesis can be the only limb salvage procedure to promote healing of the bone with comprehensive approach to all aspects of the condition. Objective of this retrospective one centred study is to perform both radiological and functional evaluation of the treatment of tibial non-unions with segmental bone defects or significant axial deviation using the method of compression - distraction osteogenesis with the Ilizarov apparatus. In the period between 2006 and 2018 15 patients were surgically treated using this method (in 9 of them as an intercalary bone transport and in other 6 as a continuous distraction with correction of axial deviation). There was an average of 22.9 months from injury and all of them underwent previous surgeries with an average of 2.3/patient.  ASAMI (Association for studying and application of Ilizarov methods) scoring system was used for both radiological (bone) and functional results. Also patientâ€™s satisfaction with the achieved results was ranked postoperatively. 80% of the patients achieved satisfactory (good and excellent) bone results and 73% satisfactory functional results. Approximately 87% of the patients were personally satisfied with the achieved results. The method of compression - distraction osteogenesis using Ilizarov apparatus proved to be effective as a limb salvage procedure with high degree of excellent and good both radiological and functional results. Keywords : compression-distraction osteogenesis, Ilizarov, non-union, bone defect https://doi.org/10.55302/JMS2142076sh